2020
DOI: 10.1016/j.adro.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of Stereotactic Body Radiation Therapy for Pulmonary Metastases in Pediatric Patients

Abstract: Purpose Pulmonary metastases are common in many pediatric solid tumors; however, little is known about safety and efficacy of lung stereotactic body radiation therapy (SBRT) for pediatric patients. We conducted a phase I/II study to investigate the minimum effective dose level of SBRT with an acceptable safety profile in pediatric patients. Methods and Materials Patients with sarcoma and metastatic pulmonary lesions ≤3 cm in diameter and ≤21 years of age were enrolled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Most commonly reported margins types were GTV-CTV and CTV-PTV margins for thoracic [44, (Fig. 2A), abdominal [15,18,30,41,45,[50][51][52][53][54][55][56]60,[62][63][64]66,70,73,74,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] (Fig. 2B), spinal [43,46,48,63,82, (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly reported margins types were GTV-CTV and CTV-PTV margins for thoracic [44, (Fig. 2A), abdominal [15,18,30,41,45,[50][51][52][53][54][55][56]60,[62][63][64]66,70,73,74,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] (Fig. 2B), spinal [43,46,48,63,82, (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other margin types for spinal treatment included PTV margins of 5 mm [99,130,131], and a GTV-PTV margin range of 7 to 10 mm [128]. Furthermore, one study reported a security margin of 3 mm for the spine [78], and in one study a 5 mm margin was reported but no margin type was specified [132].…”
Section: Resultsmentioning
confidence: 99%
“… 7 Although a number of prospective and retrospective experiences have reported on the use of SBRT for pediatric and AYA patients, each is limited by number of patients and lesions treated with larger multi-institutional trials pending analysis. 8 , 9 , 10 As such, we aimed to perform a systematic review and study-level meta-analysis of available data in the literature to characterize both the safety and efficacy of SBRT for the pediatric and AYA population.…”
Section: Introductionmentioning
confidence: 99%
“…In that group, primary tumor histologies included Ewing sarcoma ( n = 3), anaplastic chordoma ( n = 1), and osteosarcoma ( n = 1). At 6 weeks, 7/8 treated lesions had a response, but two-year local control was only 60% [ 57 ].…”
Section: Role Of Sbrt In Sarcoma For Pediatrics Adolescents and Young Adultsmentioning
confidence: 99%